Cost per Quality Adjusted Life Years Gained following Anterior Cervical Discectomy and Fusion in Elective Degenerative Pathology in Obese and Non-Obese Paients. Issue 1 (April 2016) - Chotai, Silky; Parker, Scott; McGirt, Matthew; Cheng, Joseph; Devin, Clinton
Introduction: Obese patients are at increased risk of co-morbidities and complications after spine surgery, which might result in increase cost and lower quality of life compared with their non-obese counterparts. The aim of present study was to determine the cost-utility following anterior cervical discectomy and fusion (ACDF) in obese patients. Methods: A total of 299 consecutive patients undergoing elective ACDF for degenerative cervical pathology over a period of four-years were included in the study. One and two-year medical resource utilization, missed work, and health state values (QALYs), calculated from the EQ-5D with US valuation using time weighted area under the curve approach) were assessed. Two-year resource use was multiplied by unit costs based on Medicare national allowable payment amounts (direct cost). Patient and caregiver workday losses were multiplied by the self-reported gross-of-tax wage rate (indirect cost). Total cost (direct + indirect) was used to compute cost per QALY gained. Patients were defined as obese for body mass index (BMI) ≥35 based on the WHO definition of class-II obesity. A subgroup analysis was conducted in morbidly obese patients (BMI≥ 40). Results: A significant improvement in pain (NP/AP), disability (NDI) and quality of life (EQ-5D and SF-12) was noted 2-year after surgery ( p  < 0.0001). Mean total 2-year cost was $24524 for obese patients and $22492 for non-obese patients ( p  = 0.06). Obese patients had lower mean cumulative 2-year gain in QALYs versus non-obese patients (0.39 versus 0.47 QALYs, p  = 0.19, Fig. 1). Two-year cost-utility in patients obese versus non-obese patients was $65, 805/QALY versus $47, 634/QALY. Morbidly obese patients had significantly lower (0.15) QALYs gained and significantly higher cost $168, 915/QALY gained at 2-years ( p  < 0.0001) (Table 1). Conclusion: ACDF provided a significant gain in health-state utility in obese patients, with a mean 2-year cost-utility of $65, 805/QALY gained, which can be considered moderately cost-effective. Morbidly obese patients had lower cost-effectiveness; however, surgery does provide a significant improvement in outcomes. Obesity needs to be taken into consideration as physician and hospital reimbursements move toward a bundled mode